Analysis of the Sensitivity of the Efficiency Indices of Innovative Projects to the Adjustment of Prices Related to the Product Quality - Igor Evgenevich GREKOV; Oleg Vasilyevich DOROFEEV; Sergey Vladimirovich NOVIKOV; Zhanna Vladimirovna MEKSHENEVA; Alexander Evgenevich TRUBIN (Communications of International Proceedings, 2021)
The article is devoted to the study of the issues evaluating the effectiveness of innovative projects, with respect to changes in prices for innovative goods in the future. The purpose of the study is to identify the degree of sensitivity of efficiency indicators depending on the adjustment of prices for the quality of innovative products at different levels of inflation, the size and structure of innovative projects. The authors present a methodology for calculating the project performance indicators with/without respect to the adjustment of quality prices. It is revealed that the sensitivity to the inclusion of a hedonic price index in the calculation decreases with an increase in the profitability of the project. The analysis of an experimental model based on a hypothetical project for the production of innovative products is carried out. It is revealed that for projects whose return on investment is below 20-30%, the unevenness of prices has a strong impact on the project indicators. It is proposed to use hedonic price indices for a more accurate assessment of the effectiveness of an innovative project.
Keywords: Innovations; Price Forecasting; Cash Flows; Efficiency Of An Innovative Project